How to assess the contribution of forests and wood use to climate change mitigation: Navigating through a controversial debate - Gabriele Weber-Blaschke; Matthias Dieter; Thomas Knoke; Marcus Lindner; Jürgen Bauhus (Forest Policy and Economics, 2026)

Navigating trade-offs across ownership and ecological priorities in forest conservation planning - Fabio Castelli; Jeffrey O. Hanson; Francesco Maria Sabatini; Elizabeth Law; Trishna Dutta; Marcus Lindner (Journal of Environmental Management, 2026)

The role of social, policy and economic forces in shaping forest restoration practices in Europe - Maitane Erdozain; Iciar Alberdi; Réka Aszalós; Kurt Bollmann; Vassilis Detsis; Jurij Diaci; Martina Đodan; Georgios Efthimiou; László Gálhidy; Marie Haase; Johanna Hoffmann; Delphine Jaymond; et al. (Land Use Policy, 2026)

Can “Closer-to-Nature” Forest Management Sustain Biodiversity and Ecosystem Services in an Uncertain Future? Lessons from Central Europe - Ana Stritih; Judit Lecina-Diaz; Johannes Mohr; Christian Schattenberg; Christian Ammer; Nicolò Anselmetto; Jürgen Bauhus; Andrej Bončina; Matteo Garbarino; Tomáš Hlásny; Marcus Lindner; Emanuele Lingua; et al. (Current Forestry Reports, 2026)
Purpose of Review Forests produce timber, mitigate climate change and provide important habitats; yet their capacity to provide these services under rapid global change is uncertain. “Closer-to-nature” forest management (CNFM) has been proposed by the EU Forest Strategy as a way to reconcile competing demands on forests while enhancing their resilience, but experiences with its implementation remain limited. We synthesized expert knowledge about CNFM in Central Europe, a region with a history of diverse forest management practices that has recently experienced severe impacts of climate change. We used a two-stage Delphi approach (including a questionnaire and a workshop) with experts in forest ecology and management to find a consensus about the effects of specific CNFM tools, and to identify knowledge gaps, barriers, and good practice examples of CNFM. Recent Findings A wider implementation of CNFM is likely to benefit biodiversity and ecosystem services under climate change, with only one clear trade-off identified between setting areas aside and wood production. However, limited empirical evidence exists for many of the expected effects. Substantial obstacles hinder the implementation of CNFM, including administrative constraints, social barriers, and gaps in knowledge and education. Nonetheless, we identified numerous successful cases of CNFM implementation from local to national scales in Central Europe. Summary CNFM is viewed as a potent strategy to navigate future social and ecological uncertainties, including large-scale disturbances. However, the implementation of CNFM should be adapted to the local context and ensure landscape-scale heterogeneity. Existing good practices could serve as examples for mainstreaming CNFM in Central Europe and beyond.

Biodiversity and Management as Central Players in the Network of Relationships Underlying Forest Resilience - Pilar Hurtado; Josep Maria Espelta; Luciana Jaime; Jordi Martínez‐Vilalta; Manto Samou Kokolaki; Marcus Lindner; Francisco Lloret (Global Change Biology, 2025)
Global change is threatening the integrity of forest ecosystems worldwide, amplifying the need for resilience‐based management to ensure their conservation and sustain the services they provide. Yet, current efforts are still limited by the lack of implementation of clear frameworks for operationalizing resilience in decision‐making processes. To overcome this limitation, we aim to identify reliable and effective drivers of forest resilience, considering their synergies and trade‐offs. From a comprehensive review of 342 scientific articles addressing resilience in forests globally, we identified factors shaping forest resilience. We recognized them into two categories that influence forest responses to disturbances: resilience predictors, which can be modified through management, and codrivers, which are measurable but largely unmanageable (e.g., climate). We then performed network analyses based on predictors and codrivers underlying forest resilience. In total, we recognized 5332 such relationships linking predictors or codrivers with forest attributes resilience. Our findings support the central role of biodiversity, with mixed, non‐planted, or functionally diverse forests promoting resilience across all contexts and biomes. While management also enhanced resilience, the success of specific interventions was highly context‐dependent, suggesting that its application requires a careful analysis of trade‐offs. Specifically, practices like cutting and prescribed burning generally enhanced resilience in terms of tree growth, plant diversity, landscape vegetation cover, and stand structure. In contrast, pest and herbivore control reduced the resilience of plant taxonomic diversity while offering only minimal gains for other variables. Even long‐term restoration projects showed clear trade‐offs in the resilience of different forest attributes, highlighting the need for careful consideration of these effects in practical management decisions. Overall, we emphasize that a reduced number of predictors can be used to effectively promote forest resilience across most attributes. Particularly, enhancing biodiversity and implementing targeted management strategies when biodiversity is impoverished emerge as powerful tools to promote forest resilience.

The Evolution of Forest Restoration in Europe: A Synthesis for a Step Forward Based on National Expert Knowledge - Maitane Erdozain; Iciar Alberdi; Réka Aszalós; Kurt Bollmann; Vassilis Detsis; Jurij Diaci; Martina Đodan; Georgios Efthimiou; László Gálhidy; Marie Haase; Johanna Hoffmann; Delphine Jaymond; et al. (Current Forestry Reports, 2024)
Purpose of review We are amid a historical momentum encouraging forest restoration, yet the translation of ambitious targets into reality is hindered by poor documentation and understanding of the success and failure of past restoration efforts. This review aims to evaluate the ecological, social, political and economic characteristics of forest restoration across Europe, their development over time and key lessons learned to guide future restoration initiatives. The analysis is based on the synthesis of expert assessments from 18 European countries. Recent findings Early restoration initiatives in central and southern Europe were largely reactive to natural disasters or timber shortages, and while effective in erosion control and timber production, their ecological benefits were often limited due to monoculture plantations and short-rotation systems. Geopolitical crises intensified timber production, with nationalized and centrally managed forests in several countries, but often at the cost of biodiversity. Since the 1990s, a shift toward multifunctionality has emerged driven by the convergence of environmental, social, political and economic events. Summary Forest restoration in Europe has transitioned from disaster reduction and production-driven efforts to a more multifunctional approach that promotes biodiversity. Changes have been driven by a combination of environmental (e.g., catastrophic consequences following natural disasters), political (e.g., wars, forest nationalization and management centralization), legal (e.g., strict and ambitious national and international policies), social (e.g., rural abandonment and changes in societal values) and economic (e.g., new funding mechanisms or market fluctuations) events. Despite the development, conflicting goals, insufficient funding, climate change and short-term thinking persist as key barriers.

ORF, an operational framework to measure resilience in social–ecological systems: the forest case study - Francisco Lloret; Pilar Hurtado; Josep Maria Espelta; Luciana Jaime; Laura Nikinmaa; Marcus Lindner; Jordi Martínez-Vilalta (Sustainability Science, 2024)
Resilience is commonly addressed when dealing with the sustainable planning and management of social–ecological systems, but we lack a unified framework for its quantitative assessment and application. We present an operational resilience framework (ORF) based on recognizing and relating several elements: system variables (e.g., ecosystem services), disturbances and stressors acting at given spatiotemporal scales, a reference state, and metrics comparing the observed system variables to the reference state. These elements fit into a rationale aimed at identifying resilience predictors suitable to be managed and co-drivers which describe non-manageable context, reflecting the mechanisms involved in resilience. By a systematic search of the presence of the ORF concepts in 453 empirical studies assessing resilience, we corroborate that ORF can be applied to studies on forest social–ecological systems. This literature survey shows that ORF elements are commonly recognized, although the logical narrative relating them is not always explicit, particularly in socioeconomic-focused studies. We advocate that the proposed ORF allows to standardize the terminology and to frame and measure resilience, allowing sounder comparisons and better-supported recommendations for the improvement of resilience in social–ecological systems, particularly in forest systems.

Shaping and enhancing resilient forests for a resilient society - Elena Cantarello; Jette Bredahl Jacobsen; Francisco Lloret; Marcus Lindner (Ambio, 2024)
The world is currently facing uncertainty caused by environmental, social, and economic changes and by political shocks. Fostering social-ecological resilience by enhancing forests’ ability to provide a range of ecosystem services, including carbon sequestration, habitat provision, and sustainable livelihoods, is key to addressing such uncertainty. However, policy makers and managers currently lack a clear understanding of how to operationalise the shaping of resilience through the combined challenges of climate change, the biodiversity crisis, and changes in societal demand. Based on a scientific literature review, we identified a set of actions related to ecosystem services, biodiversity conservation, and disturbance and pressure impacts that forest managers and policy makers should attend to enhance the resilience of European forest systems. We conclude that the resilience shaping of forests should (1) adopt an operational approach, which is currently lacking, (2) identify and address existing and future trade-offs while reinforcing win–wins and (3) attend to local particularities through an adaptive management approach.

Heterogenous effects of bat declines from white‐nose syndrome on arthropods - Amy K. Wray; Marcus Z. Peery; Jade M. Kochanski; Emma Pelton; Daniel L. Lindner; Claudio Gratton (Ecology Letters, 2024)
In North America, white‐nose syndrome (WNS) has caused precipitous declines in hibernating bat populations, raising the question of whether the rapid loss of arthropodivorous bats may affect the abundance of their prey. During the summers of 2015–2018 (1 year after the arrival of WNS in Wisconsin, USA), we performed intensive arthropod black‐light trapping, ultrasonic acoustic monitoring, and emergence counts at 10 little brown ( Myotis lucifugus ) and big brown ( Eptesicus fuscus ) bat maternity roosts with paired control sites. For little brown bats, which are severely affected by WNS, roost counts declined by 95% over the four‐year period, compared to a 38% decline in big brown bat roost counts. Total arthropod abundance decreased by 49%, although decreases among common little brown bat prey were less severe. Our natural predator exclusion experiment supports existing evidence that bats can have measurable trophic impacts on arthropod communities, primarily via top‐down effects on common prey.

The priorities in managing forest disturbances to enhance forest resilience: A comparison of a literature analysis and perceptions of forest professionals - Laura Nikinmaa; Johannes H.C. de Koning; Jakob Derks; Ewa Grabska-Szwagrzyk; Agata A. Konczal; Marcus Lindner; Jarosław Socha; Bart Muys (Forest Policy and Economics, 2024)

Higher site productivity and stand age enhance forest susceptibility to drought-induced mortality - Jarosław Socha; Paweł Hawryło; Luiza Tymińska-Czabańska; Björn Reineking; Marcus Lindner; Paweł Netzel; Ewa Grabska-Szwagrzyk; Ronny Vallejos; Christopher P.O. Reyer (Agricultural and Forest Meteorology, 2023)

Close-to-nature forestry and intensive forestry – Two response patterns of forestry professionals towards climate change adaptation - Dennis Roitsch; Silvia Abruscato; Marko Lovrić; Marcus Lindner; Christophe Orazio; Georg Winkel (Forest Policy and Economics, 2023)

A balancing act: Principles, criteria and indicator framework to operationalize social-ecological resilience of forests - Laura Nikinmaa; Marcus Lindner; Elena Cantarello; Barry Gardiner; Jette Bredahl Jacobsen; Alistair S. Jump; Constanza Parra; Tobias Plieninger; Andreas Schuck; Rupert Seidl; Thomas Timberlake; Kristen Waring; et al. (Journal of Environmental Management, 2023)

Significant increase in natural disturbance impacts on European forests since 1950 - Marco Patacca; Marcus Lindner; Manuel Esteban Lucas‐Borja; Thomas Cordonnier; Gal Fidej; Barry Gardiner; Ylva Hauf; Gediminas Jasinevičius; Sophie Labonne; Edgaras Linkevičius; Mats Mahnken; Slobodan Milanovic; et al. (Global Change Biology, 2023)
Over the last decades, the natural disturbance is increasingly putting pressure on European forests. Shifts in disturbance regimes may compromise forest functioning and the continuous provisioning of ecosystem services to society, including their climate change mitigation potential. Although forests are central to many European policies, we lack the long‐term empirical data needed for thoroughly understanding disturbance dynamics, modeling them, and developing adaptive management strategies. Here, we present a unique database of >170,000 records of ground‐based natural disturbance observations in European forests from 1950 to 2019. Reported data confirm a significant increase in forest disturbance in 34 European countries, causing on an average of 43.8 million m 3 of disturbed timber volume per year over the 70‐year study period. This value is likely a conservative estimate due to under‐reporting, especially of small‐scale disturbances. We used machine learning techniques for assessing the magnitude of unreported disturbances, which are estimated to be between 8.6 and 18.3 million m 3 /year. In the last 20 years, disturbances on average accounted for 16% of the mean annual harvest in Europe. Wind was the most important disturbance agent over the study period (46% of total damage), followed by fire (24%) and bark beetles (17%). Bark beetle disturbance doubled its share of the total damage in the last 20 years. Forest disturbances can profoundly impact ecosystem services (e.g., climate change mitigation), affect regional forest resource provisioning and consequently disrupt long‐term management planning objectives and timber markets. We conclude that adaptation to changing disturbance regimes must be placed at the core of the European forest management and policy debate. Furthermore, a coherent and homogeneous monitoring system of natural disturbances is urgently needed in Europe, to better observe and respond to the ongoing changes in forest disturbance regimes.

Bark Beetle Outbreaks in Europe: State of Knowledge and Ways Forward for Management - Tomáš Hlásny; Louis König; Paal Krokene; Marcus Lindner; Claire Montagné-Huck; Jörg Müller; Hua Qin; Kenneth F. Raffa; Mart-Jan Schelhaas; Miroslav Svoboda; Heli Viiri; Rupert Seidl (Current Forestry Reports, 2021)

Genetics to the rescue: managing forests sustainably in a changing world - Bruno Fady; Filippos Aravanopoulos; Raquel Benavides; Santiago González-Martínez; Delphine Grivet; Martin Lascoux; Marcus Lindner; Christian Rellstab; Fernando Valladares; Barbara Vinceti (Tree Genetics & Genomes, 2020)

Managing forest genetic resources as a strategy to adapt forests to climate change: perceptions of European forest owners and managers - Barbara Vinceti; Mattia Manica; Nina Lauridsen; Pieter Johannes Verkerk; Marcus Lindner; Bruno Fady (European Journal of Forest Research, 2020)
Managing genetic diversity is of key importance in fostering resilience of forest ecosystems to climate change. We carried out a survey reaching over 200 forest owners and managers from 15 European countries to understand their perceptions of the main threats to forest ecosystems, their knowledge of forest genetic resources (FGR) and their attitude toward actively managing these resources to strengthen the resilience of forest ecosystems to climate change. Respondents perceived pests and diseases to be the top-ranking threats to forests, followed by windstorms and drought, with differences across countries. They stated to be aware of the potential offered by managing FGR and indicated that they paid attention to origin and quality in their choice of planting material. Generally, respondents showed a positive attitude in using forest reproductive material foreign to the planting site, to better match the projected future climate conditions, introducing either a new native tree species or a new non-local genotype of a species already planted (keeping the same species but changing the source of planting material). However, forest reproductive material from local sources was largely preferred over non-local material (both genetically improved and not improved). Forest managers and owners may need to be exposed to more evidence of the potential benefits deriving from active adaptation and mitigation management of FGR before implementing adaptive measures. Also, more efforts should be invested in understanding perceptions and motivations of European forest owners and managers, in order to better tailor advice on optimal measures to counteract the detrimental effects of climate change.

Towards a roadmap for sustainable land use in Europe - Marc J. Metzger; Marcus Lindner; Bas Pedroli (Regional Environmental Change, 2018)

A cross-scale impact assessment of European nature protection policies under contrasting future socio-economic pathways - Hermann Lotze-Campen; Peter H. Verburg; Alexander Popp; Marcus Lindner; Pieter J. Verkerk; Alexander Moiseyev; Elizabeth Schrammeijer; John Helming; Andrzej Tabeau; Catharina J. E. Schulp; Emma H. van der Zanden; Carlo Lavalle; et al. (Regional Environmental Change, 2018)

Identifying pathways to visions of future land use in Europe - Pieter J. Verkerk; Marcus Lindner; Marta Pérez-Soba; James S. Paterson; John Helming; Peter H. Verburg; Tobias Kuemmerle; Hermann Lotze-Campen; Alexander Moiseyev; Daniel Müller; Alexander Popp; Catharina J. E. Schulp; et al. (Regional Environmental Change, 2018)

Carbon Accounting in Harvested Wood Products: Assessment Using Material Flow Analysis Resulting in Larger Pools Compared to the IPCC Default Method - Gediminas Jasinevičius; Marcus Lindner; Emil Cienciala; Markku Tykkyläinen (Journal of Industrial Ecology, 2018)
Summary Increasing the amount of carbon stored in harvested wood products (HWPs) is an internationally recognized measure to mitigate climate change. Several approaches and tiers of methods may be used to analyze the contribution of HWP in terms of greenhouse gas emissions and removals at a regional and national level. The Intergovernmental Panel on Climate Change (IPCC) provides guidelines on three tiers of methods for estimating annual carbon stock changes in the carbon pool of HWPs. These tiers mostly differ by the availability of input data and the level of HWP aggregation. In this case study for the Czech Republic, we have applied the production approach and alternative tiers of accounting methods, which are described in the IPCC guidelines, including the default method (tier 2) and the most advanced method (tier 3). We used country‐specific data and material flow analysis to trace the carbon flow over the entire forest‐based sector, including only the domestic harvest and the primary and secondary wood products manufactured within the country. The results of this study show that the carbon stored in the HWP pool could be underestimated if simpler methods and default values nonspecific to the country are applied. At the national level, applying the tier 3 method resulted in a 15.8% higher annual carbon inflow in the pool of HWPs compared to the tier 2 IPCC default method. This means that the advanced method reveals an apparently higher carbon sink in HWPs. A documented increase of carbon storage might bring additional credits to reporting countries, and, more important, it could promote the use of long‐life HWPs to mitigate climate change.

Changes in the spatial patterns of human appropriation of net primary production (HANPP) in Europe 1990–2006 - Christoph Plutzar; Christine Kroisleitner; Helmut Haberl; Tamara Fetzel; Claudia Bulgheroni; Tim Beringer; Patrick Hostert; Thomas Kastner; Tobias Kuemmerle; Christian Lauk; Christian Levers; Marcus Lindner; et al. (Regional Environmental Change, 2016)

Trade-Offs Between Forest Protection and Wood Supply in Europe - Pieter Johannes Verkerk; Giuliana Zanchi; Marcus Lindner (Environmental Management, 2014)

Challenges in implementing sustainability impact assessment of forest wood chains - Kaj Rosén; Marcus Lindner; Gert-Jan Nabuurs; Piotr Paschalis-Jakubowicz (European Journal of Forest Research, 2012)

Conducting sustainability impact assessments of forestry-wood chains: examples of ToSIA applications - Marcus Lindner; Wendelin Werhahn-Mees; Tommi Suominen; Diana Vötter; Sergey Zudin; Matias Pekkanen; Risto Päivinen; Martina Roubalova; Petr Kneblik; Franka Brüchert; Erik Valinger; Ludovic Guinard; et al. (European Journal of Forest Research, 2012)

Exploratory multi-criteria analysis in sustainability impact assessment of forest-wood chains: the example of a regional case study in Baden–Württemberg - Bernhard Wolfslehner; Franka Brüchert; Janine Fischbach; Werner Rammer; Gero Becker; Marcus Lindner; Manfred J. Lexer (European Journal of Forest Research, 2012)

Modelling bark beetle disturbances in a large scale forest scenario model to assess climate change impacts and evaluate adaptive management strategies - Rupert Seidl; Mart-Jan Schelhaas; Marcus Lindner; Manfred J. Lexer (Regional Environmental Change, 2009)

Impact of changing wood demand, climate and land use on European forest resources and carbon stocks during the 21st century - JEANNETTE EGGERS; MARCUS LINDNER; SERGEY ZUDIN; SÖNKE ZAEHLE; JARI LISKI (Global Change Biology, 2008)
We used the European Forest Information Scenario Model (EFISCEN) to project the development of forest resources for 15 European countries from 2000 to 2100 under a broad range of climate scenarios, which were based on the a1fi, a2, b1 and b2 storylines of the Special Report on Emissions Scenarios of the Intergovernmental Panel on Climate Change. Each climate scenario was associated with consistent land‐use change and wood demand assumptions. Climate change‐induced growth changes were incorporated into the calculations by scaling inventory‐based stem growth in EFISCEN by net primary productivity estimated from the Lund–Potsdam–Jena dynamic global vegetation model. The impact of changes in wood demand, climate and forest area were studied separately, and in combination, in order to assess their respective effects. For all climate scenarios under consideration, climate change resulted in increased forest growth, especially in Northern Europe. In Southern Europe, higher precipitation in spring and the projected increased water‐use efficiency in response to rising atmospheric CO 2 concentrations mitigated the effects of increasing summer drought. Climate change enhanced carbon sequestration in tree biomass. The climate change‐induced increase in tree growth led to a faster increase in growing stocks compared with the simulation using current climate. As productivity decreased in higher stocked forests, the positive impact of climate change began to level off during the second half of the 21st century in the scenarios where wood demand was low. Afforestation measures had the potential to increase growing stock and annual increment; however, large areas were needed to obtain notable effects. Despite noticeable differences in the growth response between the climate scenarios, changes in wood demand proved to be the crucial driving force in forest resource development. Tree carbon stocks increased by 33–114% between 2000 and 2100 when only changes in wood demand were regarded. Climate change added another 23–31% increase, while changes in forest area accounted for an additional increase of 2–40%. Our results highlight potential future pathways of forest resource development resulting from different scenarios of wood demand, land use and climate changes, and stress the importance of resource utilization in the European forest carbon balance.

Carbon inventory methods and carbon mitigation potentials of forests in Europe: a short review of recent progress - Marcus Lindner; Timo Karjalainen (European Journal of Forest Research, 2007)

Erratum to: Multiple-use forest management in consideration of climate change and the interests of stakeholder groups - Cornelia Fürstenau; Franz W. Badeck; Petra Lasch; Manfred J. Lexer; Marcus Lindner; Peter Mohr; Felicitas Suckow (European Journal of Forest Research, 2007)

Multiple-use forest management in consideration of climate change and the interests of stakeholder groups - Cornelia Fürstenau; Franz W. Badeck; Petra Lasch; Manfred J. Lexer; Marcus Lindner; Peter Mohr; Felicitas Suckow (European Journal of Forest Research, 2007)

Scaling Issues in Forest Succession Modelling - Harald Bugmann; Marcus Lindner; Petra Lasch; Michael Flechsig; Beatrix Ebert; Wolfgang Cramer (Climatic Change, 2000)

Waldbaustrategien im Kontext möglicher Klimaänderungen - Marcus Lindner (European Journal of Forest Research, 1999)